HLA‐G*01:04∼UTR3 Recipient Correlates With Lower Survival and Higher Frequency of Chronic Rejection After Lung Transplantation. Issue 9 (18th May 2015) - Di Cristofaro, J.; Reynaud‐Gaubert, M.; Carlini, F.; Roubertoux, P.; Loundou, A.; Basire, A.; Frassati, C.; Thomas, P.; Gomez, C.; Picard, C.
<x xml:space="preserve">Abstract</x> Lung transplantation (LTx) is a valid therapeutic option for selected patients with end‐stage lung disease. Soluble HLA‐G (sHLA‐G) has been associated with increased graft survival and decreased rejection episodes in solid organ transplantation. HLA‐G haplotypes named UTRs, defined by SNPs from both the 5′URR and 3′UTR, have been reported to reliably predict sHLA‐G level. The aim of this retrospective study was to determine the impact of HLA‐G alleles and UTR polymorphism from LTx recipients on anti‐HLA allo‐immunization risk, overall survival and chronic rejection (CLAD). HLA‐G SNPs were genotyped in 124 recipients who underwent LTx from 1996 to 2010 in Marseille, 123 healthy individuals and 26 cystic fibrosis patients not requiring LTx. sHLA‐G levels were measured for 38 LTx patients at D0, M3 and M12 and for 123 healthy donors. HLA‐G*01:06∼UTR2 was associated with a worse evolution of cystic fibrosis (p = 0.005) but not of long‐term survival post‐LTx. HLA‐G*01:04∼UTR3 haplotype was associated with lower levels of sHLA‐G at D0 and M3 (p = 0.03), impaired long‐term survival (p = 0.001), increased CLAD occurrence (p = 0.03) and the production of de novo donor‐specific antibodies (DSA) at M3 (p = 0.01). This study is the first to show the deleterious association of different HLA‐G alleles and UTRs in LTx.